THE ROLE OF THE DIGITAL ECONOMY IN ENSURING THE ECONOMIC SECURITY OF THE COUNTRY - Tukhtabaev, Jamshid; Razakova, Barno; Uktamov, Husniddin (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2020)
The article examines the main conditions for the development of the digital economy, the dependence of the economic development model on new means of production associated with the development of microelectronics, automation systems, information and computer technologies that generate demand for digital technologies. The current state of production facilities and related infrastructure makes digital diffusion possible, since the process is largely determined by the extent to which these technologies are used in these types of devices and equipment.